Juvenile xanthogranuloma with multiple lesions in central nervous system: A rare case report - Priyanka M Jain; P L Chandravathi; Sirisha Rani Siddaiahgari; Vijaya K Tourani (Wolters Kluwer Medknow Publications, 2016)
Juvenile xanthogranuloma (JXG) preferentially occurs in childhood and is usually benign and limited to the skin. The systemic form is rare and may be associated with severe morbidity and mortality. We describe a three and a half year old boy with disseminated papular skin lesions and neurological signs and symptoms. Diagnostic workup revealed multiple brain lesions. Skin and brain biopsy was suggestive of systemic JXG. Treatment with prednisolone, vinblastine, and methotrexate caused regression of skin and central nervous system (CNS) lesions. However, 6 months after completion of chemotherapy, cutaneous but not CNS lesions relapsed. Few case reports have been published in the past, particularly with multiple lesions in CNS, which as in our case, is an extremely rare finding.